(untitled) (The Research of Medical Science Review, 2025)
Background: Anxiety is an emotional state characterized by a heightened sense of self-protection oriented toward future events. Depression, on the other hand, is a mood disorder marked by persistent feelings of sadness, loss of interest or pleasure, and emotional numbness Objectives: To evaluate levels of anxiety depression among undergraduate students of nursing Methods: A cross-sectional research design was employed, involving a sample of 112 undergraduate nursing students from Jesus and Mary Institute of Nursing and St. James Institute of Nursing, Karachi. Data were collected using a socio-demographic questionnaire and the Aga Khan University Anxiety and Depression Scale (AKUADS) Results: The findings of the study revealed that 64.3% of nursing students exhibited positive Anxiety Depressive Symptoms (ADS), while 35.7% showed negative ADS. The analysis of ADS in relation to socio-demographic variables demonstrated no statistically significant associations with age, gender, residence, academic level, job status, or substance use. Additionally, a very weak and statistically insignificant negative correlation was observed between Anxiety Depressive Symptoms (ADS) and age (r = -0.083; n = 112; p = 0.382) Conclusion:The findings of the current study indicate that the majority of nursing students were experiencing symptoms of anxiety and depression. Furthermore, socio-demographic variables—including gender, academic year, residence, job status, and substance abuse status—did not have a statistically significant impact on these symptoms. These results underscore the urgent need for targeted interventions aimed at reducing anxiety and depression levels among nursing students, given their crucial role as the future of the nursing profession.